Modelo de gestión comercial para fortalecer la competitividad en la Coop. Sac sucursal Atuntaqui. - Vitar, Carlos (2020)
This research proposes a Business Management Model to strengthen the competitiveness of the Cooperativa de Ahorro y Crédito Indígena SAC Ltda. Atuntaqui Branch, this document consists of three chapters such as: theoretical framework, methodological development, research results, as well as conclusions and recommendations in each of the chapters and at the end of the document in a general way and we will finish with the proposal of Commercial Management.